Synthesis and study of the optical, structural and morphological properties of TiO2:Co alloys prepared by Co-Sputtering (2018)
In this work, cobalt-doped titanium dioxide thin films were synthesized using the advantageous DC Magnetron Co-sputtering method varying different fabrication parameters like deposition time, substrate temperature and type of substrate employed; a portion of the fabricated samples was then subject to annealing processes in uncontrolled atmosphere. The resulting material was an opaque, seemingly uniform thin film of black appearance which became more transparent and brown-like after annealing at temperatures beyond 500 °C. The fabricated samples were submitted to structural, morphological, optical, compositional and magnetic characterizations, evidencing a limited crystallization, low grain size (less than 200 nm), elevated reflectance (up to 95% in the IR region), low transmittance (less than 0.8% for cobalt-containing samples) and superparamagnetic behavior of the as-deposited thin films, which, after the annealing processes were performed, became severely more crystalline, transparent and increased their grain size (reaching values of even 1000 nm), maintaining its granular morphology in the surface. Cobalt oxide (Co3O4) and cobalt titanate (CoTi2O5) were among the crystalline phases found via X-ray diffraction, the latter pertaining a spinel-like structure in which the cobalt atoms exist in two separate oxidation states, namely +2 and +3. These results prompted the successful conclusion of the fabrication of an intermetallic alloy thin film, which in turn supports one of the main contributions of this work to the materials science research field. The synthesis of the ternary CoTi2O5 phase with this configuration of the sputtering technique had not, until now, yet been reported.